Middle Ear Barotrauma in Military Aircrew: Analysis of Risk Factors (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Middle ear barotrauma is a common medical problem related to aviation; because the aviation environment exposes the aviator to a rapidly changing ambient pressure. Middle ear barotrauma occurs when the Eustachian tube failed to equalize middle ear pressure with ambient pressure during flight.Objective: To determine the prevalence of middle ear barotraumas among aircrew on Bangladesh Air Force (BAF) and to find the risk factors of middle ear barotrauma.Materials and Methods: This cross-sectional study was carried out on middle ear barotrauma in aircrew of BAF from February 2018 to January 2019. Aircrew who experienced fullness in the ear or ear pain during flight and visited the flight surgeon was enrolled in this study. Modified TEED scale used for grading of middle ear barotrauma.Results: The study revealed middle ear barotrauma in the aircrew was 12.0% with a higher prevalence among the student pilots (14.2%) compared with trained pilots (5.9%), the mean age of aircrew was 23.2 ± 3.6 years. The right ear (43.5%) was affected in most of the cases than the left ear (34.8%). Most of the symptoms developed at a stage of descending (60.9%). The duration (mean± SD) of sickness was 7.6±3.7 days.Conclusion: Middle ear barotrauma or ear block is common in trainee aircrew but it is also seen in the experienced pilots who fly with upper respiratory tract infection (URTI) or a common cold. Appropriate training on ear physiology related to pressure changes inside the hypobaric altitude chamber can prevent the incidence of middle ear barotrauma.JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 14-17